Multiparadigma Sosiologi Hukum Keluarga Islam - Abdul Haq Syawqi (Fakultas Syariah IAIN Madura, 2022)
This paper elaborate various paradigms in contradictory and relatively ambiguous in sociological of Islamic family law in Indonesia. The discussion will be focused on the paradigm of the sociology of law and developed on the Islamic law also its implication in social aspects. By using an interdisciplinary approach with a normative-juridical study, the aim of this paper is to solve various social problems. This model is very crucial to be carried out immediately. The result show that the paradigms provide several new points of view and very useful in solving various problems in the study of administrative of marriage, inheritance and the age of marriage